ANALISIS PENGGUNAAN MEDIA GAMBAR FLASHCARD TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS DALAM MATERI “ AKU DAN LINGKUNGAN SEKITARKU” DI KELAS III SD 060925 MEDAN - Maulida Syakira Nasution; Safrida Napitupulu; Rosmawati Harahap; Nila Lestari (STKIP Subang, 2026)
The purpose of this study was to determine the influence, increase in student learning interest and the effectiveness of the use of flashcard image media on the understanding of grade III SD students in studying the material